Stem Cell-Based Therapy for Experimental Ischemic Stroke: A Preclinical Systematic Review - Zhang, Xi-Le; Zhang, Xiao-Guang; Huang, Yan-Ran; Zheng, Yan-Yan; Ying, Peng-Jie; Zhang, Xiao-Jie; Lu, Xiao; Wang, Yi-Jing; Zheng, Guo-Qing (Frontiers in Cellular Neuroscience, 2021)
Stem cell transplantation offers promise in the treatment of ischemic stroke. Here, we utilized systematic review, meta-analysis, and meta-regression to study the biological effect of stem cell treatments in animal models of ischemic stroke. A total of 97 eligible publications were included by searching PubMed, EMBASE, and Web of Science from inception to August 1, 2020. There are about one hundred and thirty-nine comparisons involving 5222 animals examined the effect of stem cell transplantation on the neurological function and the infarct volume as primary outcome measures in animal models for stroke. Stem cell-based therapy can improve both neurological function (effect size, -3.45, 95% Confidence Interval, -3.95 to -2.96) and infarct volume (effect size, -11.37, 95% Confidence Interval, -12.9 to -9.84) compared with controls. These results suggest that stem cell therapy could improve neurological function deficits and infarct volume, exerting potential neuroprotective effect for experimental ischemic stroke. But further clinical studies are still needed.